Strategi Penerapan Metode Langsung untuk Menumbuhkan Kemampuan Keterampilan Berbicara (Maharah al-Kalam) Santri - Ukasyah Ukasyah; Itsnaini Muslimati Alwi (ALSYS, 2026)
The low speaking skills (maharah al-kalam) of students in Arabic language learning remain a problem influenced by limited vocabulary, low self-confidence, and minimal communication practice in real contexts. This study aimed to describe teachers’ strategies in applying the direct method and to identify supporting and inhibiting factors in the development of students’ speaking ability at MTs Darul Hijroh Canden. This study used a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, and were then analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing, while validity was tested through source and technique triangulation. The results showed that the strategy for applying the direct method was carried out through the integration of four main approaches, namely the creation of bi’ah lughawiyah or a language environment, hiwar or dialogue practice, role play, and the habituation of daily communication using Arabic. This strategy was able to improve students’ speaking ability, particularly in terms of fluency, confidence, and accuracy in language use. The main supporting factors included a conducive pesantren environment and students’ motivation, whereas the inhibiting factors included limited vocabulary and low self-confidence. The conclusion of this study confirms that the success of the direct method is largely determined by teachers’ consistency in integrating communicative and contextual learning strategies as well as the support of a sustainable language environment. The implications of this study indicate the importance of developing Arabic language learning based on communication and environment (language immersion) that pays balanced attention to students’ linguistic and psychological aspects.